Influence of aggregate gradation and compaction on compressive strength and porosity characteristics of pervious concrete - Anburuvel, A.; Daniel Niruban, S. (Taylor & Francis Group, 2022)
This study examined the influence of aggregate gradation on compressive strength and porosity in Pervious Concrete (PC) subjected to various compaction efforts. Two aggregate gradations 12–18 and 18–25 mm were recombined in different proportions in the range of 10–50% to obtain five different gradations. PC specimens were cast with these five aggregate gradations by applying standard Proctor compaction, varying efforts from 0 to 75 blows. Test results indicated that wet density and compressive strength increased with compaction effort at higher rate for specimens casted with Aggregate-to-Cement (A/C) ratio 2.5 than 5.0, but porosity reduced at almost the same rate for both A/C ratios. Compressive strength reduced when aggregate gradation with larger size particles increased, however porosity increased. Altering aggregate gradation or compaction effort yielded no significant change in PC properties for A/C ratio of 5.0 than it did for 2.5. The developed mathematical models predicted compressive strength and porosity of PC mixes in terms of aggregate gradation and compaction effort. The highest mean deviation and relative error of model prediction were 1.377 MPa and 10.4% for compressive strength, and 1.414% and 5.8% for porosity, respectively.
Keywords: Pervious concrete; Porosity; Compressive strength; Aggregate gradation; Aggregate-to-cement ratio